2019
DOI: 10.1108/tldr-03-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

Online risk for people with intellectual disabilities

Abstract: Purpose: This review summarises the current state of empirical knowledge pertaining to online risk and cybercrime relating to people with intellectual disabilities (ID). Approach: This narrative review summarises, synthesises and critically evaluates the current literature and state of knowledge and offers suggestions for extending current knowledge and practice. Findings: Evidence regarding risk for people with ID is limited but growing. Existing findings highlight that: (i) risk may increase contingent upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 31 publications
0
52
0
8
Order By: Relevance
“…Parents are often the ones providing support, and the results demonstrating that parents of adolescents with ID are more positive about internet use compared to a reference group of parents is an important finding. It is also counterintuitive and does not match previous research, where it has been suggested that factors such as poor insight and difficulty with problem-solving skills put people with ID at greater risk when using the internet (Chadwick, 2019). However, recent studies have revealed that parents state that the opportunities outweigh the risks with the internet (Molin et al, 2019).…”
Section: Opportunities and Risksmentioning
confidence: 83%
See 1 more Smart Citation
“…Parents are often the ones providing support, and the results demonstrating that parents of adolescents with ID are more positive about internet use compared to a reference group of parents is an important finding. It is also counterintuitive and does not match previous research, where it has been suggested that factors such as poor insight and difficulty with problem-solving skills put people with ID at greater risk when using the internet (Chadwick, 2019). However, recent studies have revealed that parents state that the opportunities outweigh the risks with the internet (Molin et al, 2019).…”
Section: Opportunities and Risksmentioning
confidence: 83%
“…This has been highlighted in previous research, i.e. that not having access to internet-enabled devices or digitally participating make the prevalence of risk experiences low according to parents, and difficult to foresee (Chadwick, 2019). Parents of adolescents in general have been shown to have more concerns about online safety related to more time being spent on the internet by the adolescent (Sorbring, 2014).…”
Section: Opportunities and Risksmentioning
confidence: 91%
“…2015), or safety concerns (Chadwick et al . 2017; Chadwick 2019). Our findings point more to which interactions are possible with the technologies.…”
Section: Discussionmentioning
confidence: 99%
“…These researchers concluded that positive experiences were associated with higher levels of engagement with social media and that its use resulted in increased self‐esteem and development of social identity. Although numerous benefits of social and digital inclusion have been identified by researchers, there has been little consideration of possible unintended effects of digital inclusion beyond issues of safety relating to vulnerability to cyber‐crime (Chadwick 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This situation highlights the importance of teachers' training in order to implement online risks mediation strategies that favour the safe use of the Internet by their students with ID (Kalmus, von Feilitzen, & Siibak, 2012). However, there are still very few studies that address this issue (Normand & Sallafranque-St-Louis, 2016), and they are even less so in the field of special education teachers (Chadwick, 2019).…”
Section: Introductionmentioning
confidence: 99%